Ado????o de inova????o organizacional: o caso do balanced scorecard (BSC) em empresas no Brasil - Lopes, Ant??nio Carlos Vaz (2013)
The general objective of this work is to understand the process of adoption of an organizational innovation , in this case (BSC), in three of major Brazillian companies using the theory of diffusion of innovation (TDI). In order to answer the questions proposed in the study a qualitative research approach is used, to permit to explore in detailed form the experiences of the participants, in the adoption process of innovation much like the effects of BSC on organization. The strategy used was the study of multiple cases incorporated in three major Brazillian organizations. The data was collected mainly through in-depth semi-structured interviews with the main parties involved in the decision process of adoption, implementation and the main users of BSC. The data obtained in the interviews and documents from the companies were analyzed through the analysis technique contained in Bardim (2003) and inter-case and intra-case analysis suggested by Miles and Huberman (1994). The results of the study show that the companies adopted BSC as a mechanism to obtain efficiency through the use of performance evaluation implementation and communication and strategic management. The decision for BSC was made by the senior management who had an effective involvement and provided all the support necessary so that the same can become part of the company routine. Managers at all levels of the organization participated in the adoption process. It concludes that the attributes relative advantage, ease of use and compatibility were indentified as the main influencers in the adoption of BSC, in relation to internal factors three were identified as influencers: type of communication channels used, the type of decision, the role played by agents of change at different levels of organization being the last main internal factor that contributed to the adoption of BSC. In this way the factors which influenced the decision of the adoption of BSC in organizations can be explained by the theory of diffusion of innovation.